A RURAL LANDSCAPE READING THROUGH CONTINUITY AND CHANGE: GOLOVA RURAL NEIGHBORHOOD (VILLAGE) IN ELMALI DISTRICT OF ANTALYA PROVINCE - Akdegirmen Ercan, Selin; Gencer, Ceylan Irem (E.U. Printing and Publishing House, 2024)
Rural areas represent significant zones where urban and natural environments intersect, showcasing the connection between humans and nature. Historic rural landscapes are comprised of a system in which tangible and intangible components such as natural, historical-cultural, social, economic, political, ideological, symbolic, environmental, and ecological factors collaboratively operate. These areas, like Palimsest, are multi-layered and contain many historical traces. It is not the result of an individual, but of a whole community, not a programmed and planned project, but the result of techniques passed down and developed from generation to generation. Although these areas, where life flows in cycles, have undergone major changes over time with external interventions. Many traces of the place continue to exist in the rural area and its biggest component, architecture. Settlements in rural areas do not exist on their own. It maintains its existence as a network in relation to the surrounding areas and settlements. Based on the necessity of understanding these environments as a whole, the rural area of Antalya Province Elmal & imath; District, which constitutes holistic relationship between settlements and areas, has been determined as the sample area. In this study, the environmental area and settlement pattern of Semay & uuml;k/M & uuml;& gbreve;ren Plain of Elmal & imath; District and G & ouml;lova (M & uuml;& gbreve;ren) village were investigated, and the conservation problems of the area were examined. Elmal & imath; District, located in the west of Antalya Province, is a fertile region with alluvial-covered plains. It has been determined that the settlement history of this area on the Taurus Mountains goes back to the Neolithic Age, and it has been the dominion area of many civilizations. Semay & uuml;k/M & uuml;& gbreve;ren Plain is located in the north-east of Elmal & imath; center. The architectural characteristics of the settlements are similar to each other in the plain. G & ouml;lova is an important settlement where the changes experienced over time and traces from the past can be seen. Surrounded by vineyards, seasonal pastures, secondary settlement areas (Kasaba), ritual spaces, and communal zones, the settlement forms a cohesive whole. In the area surrounding the archaeological site, there are numerous spolia materials found. The houses built using the mudbrick construction technique, which has been developed and employed in the region for generations, along with their extensions like granaries, bread ovens (ekmeklik), sheep shelter, stables, and haylofts, create a texture that emerges from the symbiosis of the natural environment and traditions. Presently in G & ouml;lova, no craftsmen continue the traditional construction techniques, leading to the abandonment of some rural structures that are incompatible with contemporary conditions. Additional structures are added to some of these buildings using modern materials. The mudbrick dwellings in the vineyards have collapsed, and concrete structures have been erected in some of these spaces. Although livestock farming persists today, the number of households participating in highland migration has significantly decreased, and the traditional shelters in the highlands are no longer in use. Since rural areas are undergoing rapid transformation, rapid documentation is of great importance. While developing conservation strategies, it is necessary to act with the awareness that human life in the countryside is a part of natural life, and the relationship of all dynamics of the place with each other should be considered.
Keywords: Historic rural landscapes; rural settlements; rural architecture; vernacular architecture; Elmal & imath; G & ouml; lova village; Art